Prediction of Ki-67 expression in bladder cancer based on CT radiomics nomogram - Feng, Shengxing; Zhou, Dongsheng; Li, Yueming; Yuan, Runqiang; Kong, Jie; Jiang, Feng; Chen, Weitian; Zhang, Lijie; Gong, Mancheng (Frontiers in Oncology, 2024)
Objectives: To create and validate a radiomics nomogram for non-invasive preoperative Ki-67 expression level prediction in patients with bladder cancer (BCa) using contrast-enhanced CT radiomics features. Methods: Retrospective analysis of 135 patients, 79 of whom had high levels of Ki-67 expression and 56 of whom had low levels. For the dimensionality reduction analysis, the best features were chosen using the least absolute shrinkage selection operator and one-way analysis of variance. Then, a radiomics nomogram was created using multiple logistic regression analysis based on radiomics features and clinical independent risk factors. The performance of the model was assessed using the Akaike information criterion (AIC) value, the area under the curve (AUC) value, accuracy, sensitivity, and specificity. The clinical usefulness of the model was assessed using decision curve analysis (DCA). Results: Finally, to establish a radiomics nomogram, the best 5 features were chosen and integrated with the independent clinical risk factors (T stage) and Rad-score. This radiomics nomogram demonstrated significant correction and discriminating performance in both the training and validation sets, with an AUC of 0.836 and 0.887, respectively. This radiomics nomogram had the lowest AIC value (AIC = 103.16), which was considered to be the best model. When compared to clinical factor model and radiomics signature, DCA demonstrated the more value of the radiomics nomogram. Conclusion: Enhanced CT based radiomics nomogram can better predict Ki-67 expression in BCa patients, and can be used for prognosis assessment and clinical decision making.